2017
DOI: 10.17219/acem/29849
|View full text |Cite
|
Sign up to set email alerts
|

The effects and safety of intravitreal triamcinolone injections in the treatment of diabetic macular edema

Abstract: Background. Diabetic macular edema (DME) is responsible for three-quarters of vision-loss cases in diabetic eye disease. In most cases, early treatment by laser photocoagulation can only stabilize vision. Glucocorticoids have been used as a local pharmacological treatment in DME when the inflammation seems to have a pathological background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 14 publications
0
16
1
Order By: Relevance
“…Intraocular corticosteroids are frequently used in clinical practice to treat macular edema, because they are effective and generally have a longer duration of action and a lower administration frequency than anti-VEGF agents. 2,8,9,[17][18][19][20] Steroids are preferable in pseudophakic eyes with persistent/recurrent macular edema and in cases of intolerance or contraindication to anti-VEGFs. 2 Although intraocular corticosteroids are generally considered safe, one of their main complications is the increase in IOP, with possible development of OHT or even glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Intraocular corticosteroids are frequently used in clinical practice to treat macular edema, because they are effective and generally have a longer duration of action and a lower administration frequency than anti-VEGF agents. 2,8,9,[17][18][19][20] Steroids are preferable in pseudophakic eyes with persistent/recurrent macular edema and in cases of intolerance or contraindication to anti-VEGFs. 2 Although intraocular corticosteroids are generally considered safe, one of their main complications is the increase in IOP, with possible development of OHT or even glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…In another longlasting diabetes study, Müller cells were still found to express upregulated GFAP levels after 20 weeks. 91 Importantly, administration of aflibercept 35 or TAAC, 36 were able to significantly reduce both inflammation and macrogliosis at 8 weeks after diabetes onset, which highlight the fact that the mouse STZ model can be used to study novel therapies for DR that halt the inflammatory response. The opposite effect of aflibercept on neurodegeneration and inflammation can be explained by the fact that, although both neuronal and inflammatory cells express VEGF-receptors, both cell types will exert different functions upon ligand binding.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of mice was intravitreally (IVT) injected with compounds that are currently used in clinical practice for the treatment of DR, aflibercept (Eylea; Bayer, Leverkusen, Germany) and triamcinolone acetonide (TAAC, Kenacort; Bristol-Myers Squibb, New York, NY, USA). 35,36 Mice were deeply anesthetized via inhalatory isoflurane (4% Iso-Vet; Dechra, Northwich, UK) and the eyes were further locally anesthetized with oxybuprocaine (0.4% Unicaine; Thea Pharma, Wetteren, Belgium) eye drops. IVT injections (1 lL) were performed with a small glass capillary (50-70 lm diameter), connected to a microinjector (Micro4, microsyringe pump controller; World Precision Instruments, Sarasota, FL, USA).…”
Section: Intravitreal Administration Of Compoundsmentioning
confidence: 99%
“…[ 9 ] Intravitreal triamcinolone carried higher risks to induce IOP raising, cataract formation, and endophthalmitis than PSTA in a prior multicenter investigation. [ 8 9 10 20 ] Furthermore, PSTA showed 2.4 times lower risk of associated IOP elevation than anterior subtenon triamcinolone injection. [ 21 ] Therefore, we added PSTA on routine IVR for these refractory diabetic patients, in order to enhance the efficacy of macular edema control and lower the possibility of postinjection ocular hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 9 ] Higher incidence of complications, such as elevated intraocular pressure (IOP), cataract formation, and endophthalmitis, was found following intravitreal injection of triamcinolone acetonide compared to subtenon administration. [ 8 9 10 ]…”
Section: Introductionmentioning
confidence: 99%